Sabhamandapa at the Vyankatesh Balaji Temple - Ghosh, Ayan (2023)
The sabha mandap at Vyankatesh Balaji temple has sophisticated woodwork and pradakshina corridor around the garbagriha. The use of timber columns and arched panels reflects architecture from the Peshwa period. The present temple was constructed in 1781 by a devotee named Diveshankar, on the site of an older Koli temple.